2019
DOI: 10.1039/c9cc02510c
|View full text |Cite
|
Sign up to set email alerts
|

Highly enhanced durability of a graphitic carbon layer decorated PtNi3 alloy electrocatalyst toward the oxygen reduction reaction

Abstract: An N-doped graphitic carbon layer was for the first time introduced to greatly enhance the durability of a PtNi3/C alloy catalyst in an acidic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…A higher stability was additionally observed on the PtFe alloy due to the ordered atomic arrangement and robustness of the N-doped carbon nanoshell. Moreover, a PDA-derived N-doped graphitic carbon layer (NGC, 0.76 nm thickness) was overcoated on the carbon-supported PtNi 3 alloy catalyst to overcome the stability issue under acidic conditions, as reported by Sun et al 231 In the preparation process, overcoating as-synthesized PtNi 3 /C with the PDA layer was first performed, followed by high-temperature pyrolysis to obtain the final catalyst, which was named PtNi 3 /C@NGC. Structural characterization indicated that the PtNi 3 particle holds the merit of a Pt-rich surface and a Ni-rich core, likely attributed to the higher adsorption energy of Pt with N atoms (from PDA coating) than that of Ni.…”
Section: Overcoated Precious Metal Based Orr Electrocatalystsmentioning
confidence: 99%
“…A higher stability was additionally observed on the PtFe alloy due to the ordered atomic arrangement and robustness of the N-doped carbon nanoshell. Moreover, a PDA-derived N-doped graphitic carbon layer (NGC, 0.76 nm thickness) was overcoated on the carbon-supported PtNi 3 alloy catalyst to overcome the stability issue under acidic conditions, as reported by Sun et al 231 In the preparation process, overcoating as-synthesized PtNi 3 /C with the PDA layer was first performed, followed by high-temperature pyrolysis to obtain the final catalyst, which was named PtNi 3 /C@NGC. Structural characterization indicated that the PtNi 3 particle holds the merit of a Pt-rich surface and a Ni-rich core, likely attributed to the higher adsorption energy of Pt with N atoms (from PDA coating) than that of Ni.…”
Section: Overcoated Precious Metal Based Orr Electrocatalystsmentioning
confidence: 99%
“…Previous studies have shown that metal oxide layers can effectively suppress the aggregation of NPs [55,131,132]. However, such protective coatings may limit metal atoms' mobility, which would increase the energy barrier of metal NP crystal structure transitions, bringing difficulty in forming fully ordered intermetallic phases even at high temperatures [90,133].…”
Section: Oxide Coatingsmentioning
confidence: 99%
“…Various carbon coatings have also been used to prevent the aggregation of NPs during their high-temperature transitions [127,131,142,143]. For example, Chung et al [144] covered pre-synthesized PtFe NPs with a PDA layer.…”
Section: Carbon Coatingsmentioning
confidence: 99%
“…2 b and d). According to XPS analysis, the components of the associated outer layer were mainly graphitic nitrogen and graphite which could be assigned to disordered graphitic carbon and nitrogen (C x N y ) [21] . As illustrated in Fig.…”
Section: Haadf-tem and Element Mappingmentioning
confidence: 99%